SISTEM PAKAR UNTUK MENENTUKAN ALTERNATIF KEPUTUSAN MENGGUNAKAN METODE EXPECTED PAY OFF (EP) DAN EXPECTED LOSS (EL) - Risanto, Joko (Jurnal Pilar Sains, 2007)
Decision making basically is choose an alternative. Chooses a decision often bewilders because variousfactors between it. firstly, lack of information causing height of Un-expected Value and second, plenty ofconsideration that causes choice taken is irrational. in general, wrong decision can cause imprecise action andgenerates loss. Some mathematical models has been developed to calculate and analyses every choice indetermining a decision. one of them is Expected Pay Off and Expected Loss mehod. manually that methodwould be difficult and needs time to calculate. Therefore need to exploit ability of computer to calculatequickly and gives objectively and rational solution to userfirst step of this systems development is by mapping mathematically number of alternatives which will beselected and advantage value percentage or loss from every the alternative. hereinafter every value is input tocomputer and processed applies mathematical equation :EP will be calculated repeatedly and compared to every result of its. the expected information from thissystem is an an alternative Information that is most rational for user. The Result indicates that theapplication of competent this and can be applied.Keywords : Expected loss, Expected Pay Off, Decision making.